Time, media and modernity - Keightley, Emily, 1981- (Palgrave Macmillan, 2012)
" A wide ranging, interdisciplinary exploration of media time and mediated temporalities. The chapters explore the diverse ways in which time is articulated by media technologies, the way time is constructed, represented and communicated in cultural texts, and how it is experienced in different social contexts and environments."--